78‐3: 2D Representation of Display Color Gamut. Issue 1 (30th May 2018) - Masaoka, Kenichiro; Jiang, Fu; Fairchild, Mark D.; Heckaman, Rodney L.
Abstract : Display gamuts usually render complex shapes in a uniform color space, requiring observers to change views to comprehend a 3D plot. We propose a 2D representation of a display color gamut, named "gamut rings, " where the area within an arbitrary luminance and hue angle range corresponds to gamut volume.